Novel Titanium Implant: A 3D Multifunction Architecture with Charge‐Trapping and Piezoelectric Self‐Stimulation (Adv. Healthcare Mater. 11/2023). Issue 11 (26th April 2023) - Sun, Lei; Chen, Xuzhuo; Ma, Kun; Chen, Ruiguo; Mao, Yi; Chao, Rui; Wang, Hui; Yu, Bin; Wang, Junfeng; Zhang, Shanyong
Abstract : Anti‐Inflammatory Materials In article 2202620 by Bin Yu, Junfeng Wang, Shanyong Zhang and co‐workers, a 3D multifunctional architecture is developed with antibacterial, anti‐inflammatory, and osteointegration properties. Charge‐trap‐based antibacterial and piezoelectrically self‐stimulated anti‐inflammatory responses are achieved to enhance osteointegration of titanium implants.